Antiplatelet Therapy in Primary Spontaneous and Oral Anticoagulation-Associated Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Stroke, 2018)
Background and Purpose- This study determined the influence of concomitant antiplatelet therapy (APT) on hematoma characteristics and outcome in primary spontaneous intracerebral hemorrhage (ICH), vitamin K antagonist (VKA)- and non-VKA oral anticoagulant-associated ICH. Methods- Data of retrospective cohort studies and a prospective single-center study were pooled. Functional outcome, mortality, and radiological characteristics were defined as primary and secondary outcomes. Propensity score matching and logistic regression analyses were performed to determine the association between single or dual APT and hematoma volume. Results- A total of 3580 patients with ICH were screened, of whom 3545 with information on APT were analyzed. Three hundred forty-six (32.4%) patients in primary spontaneous ICH, 260 (11.4%) in VKA-ICH, and 30 (16.0%) in non-VKA oral anticoagulant-associated ICH were on APT, and these patients had more severe comorbidities. After propensity score matching VKA-ICH patients on APT presented with less favorable functional outcome (modified Rankin Scale score, 0-3; APT, 48/202 [23.8%] versus no APT, 187/587 [31.9%]; P=0.030) and higher mortality (APT, 103/202 [51.0%] versus no APT, 237/587 [40.4%]; P=0.009), whereas no significant differences were present in primary spontaneous ICH and non-VKA oral anticoagulant-associated ICH. In VKA-ICH, hematoma volume was significantly larger in patients with APT (21.9 [7.4-61.4] versus 15.7 [5.7-44.5] mL; P=0.005). Multivariable regression analysis revealed an association of APT and larger ICH volumes (odds ratio, 1.80 [1.20-2.70]; P=0.005), which was more pronounced in dual APT and supratherapeutically anticoagulated patients. Conclusions- APT does not affect ICH characteristics and outcome in primary spontaneous ICH patients; however, it is associated with larger ICH volume and worse functional outcome in VKA-ICH, presumably by additive antihemostatic effects. Combination of anticoagulation and APT should, therefore, be diligently evaluated and restricted to the shortest possible time frame.
EVALuna2:34909